(untitled) (Perner’s Contacts, 2020)
The paper deals with the life cycle of electric vehicle and future of reusing and recycling its battery. Investing in new alternative propulsion became an obligation to every automotive company because of the latest emissions limits. The life cycle is divided into three phases which describes a phase of production, phase of use and phase of recycling. Each of the phases has its own strategy and source of emissions. Research is focused on possible options how emissions can be reduced which helps to understand the importance of the problem. The main attention is paid to future options of reducing emissions in the recycling and reusing process, also an article focus on the analysis of expected battery life of an electric vehicle based on a comparison of selected models.